The Role of Sensory Fiber Demography in Trigeminal and Postherpetic Neuralgias - DaSilva, A.F. (SAGE Publications, 2012)
In this study, we systematically investigated fiber demography, based on function and distribution, from the periphery to their destinations in the various central (sub) nuclei in the trigeminal brainstem nuclear sensory complex. Conventional and novel compelling information is provided, demonstrating that the ratio and somatotopy of types A and C sensory fibers at the site of a lesion can elucidate important puzzles in TNP disorders. For instance, we explain how of a major shift in the fibers’ direction and ratio at the level of the trigeminal root entry zone (REZ) influences the pathophysiology of pre- and typical trigeminal neuralgia. As a result, there is a high A/C ratio of oral and peri-oral fibers in the supero-medial region of the REZ, which is mostly susceptible to vascular compression. However, this A/C ratio varies considerably at lower proportions in other areas along the peripheral trigeminal pathway, where an injury (viral, vessel compression, or trauma) can lead to a broader spectrum of fiber involvement and, consequently, pain outcome. In summary, we explain how fiber demography can influence pain quality, location, temporal features, progress, and treatment prognosis of TNP in those patients who develop it.